COMMUNICATION WITH THE OUTSIDE WORLD AS A PREREQUISITE FOR THE RESOCIALIZATION AND SOCIAL REINTEGRATION OF CONVICTED PERSONS - Grujić, Zdravko; Milić, Ivan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
The position of a convicted person serving a prison sentence is determined in multiple ways and depends on numerous factors. Basically, the normative framework defines the rights, obligations and responsibilities of convicted persons serving a prison sentence and determines the rules and expected behavior of convicted persons in penitentiary institutions. Their position also depends on the institution where the imprisonment is executing and to which the person is sent to serve the sentence, the architectural arrangement, spatial and functional capacities of the institution, the structure of the convict population, the convict subculture, security, assessment of the degree of risk, the established program for dealing with the convicted person and numerous other circumstances. The scope of basic rights, especially extended rights (conveniences) of convicted persons depends on the category assigned to the convicted person, but also on the fact that determines whether it is a convicted person who represents part of the general prison population or a convict who belongs to a special prison population. Exercising the rights, above all the rights to communicate with the outside world of convicted persons, is indisputably a prerequisite for the successful implementation of the treatment program and the realization of resocialization, but also the social reintegration of the convicted person after serving his sentence. The authors, as a logical continuation of the work that analyzed the rights of convicted persons to visit family members and establish contacts outside the institution, using, first of all, the normative-legal method, analyzed the rights of convicted persons that are related to communication with the outside world and are provided for in the basic laws in the field of criminal-enforcement law and by-laws and refer to both categories prison population. The goal of the work is to indicate to what extent the realization of communication with the outside world of the convict is a prerequisite for successful communication, implementation of the treatment program, realization of resocialization as an one of the purpose of punishment, i.e. enabling social reintegration into the community after serving the sentence.
Keywords: communication with the outside world; rights of convicted persons; prison sentence